Exact Solutions with Lie Symmetry Analysis for Nano-Ionic Currents along Microtubules - Yuzbasi, Zuhal Kucukarslan; Aslan, Ebru Cavlak; İnç, Mustafa (E D P Sciences, 2018)
In this work, the Lie symmetry analysis is tested by its applications to nano-solitons of ionic waves propagation along microtubules in living cells and nano-ionic currents of MTs.
3rd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 04-06, 2018 -- Final Int Univ, Girne, CYPRUS
Keywords: Conservation-Laws; Solitons; Equation; Model